2022
DOI: 10.1038/s41598-022-23806-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence, detailed characterization and clinical context of complement activation in acute multisystem inflammatory syndrome in children

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a rare, life-threatening complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. MIS-C develops with high fever, marked inflammation and shock-like picture several weeks after exposure to, or mild infection with SARS-CoV-2. Deep immune profiling identified activated macrophages, neutrophils, B-plasmablasts and CD8 + T cells as key determinants of pathogenesis together with multiple inflammatory markers. The disease rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Previous adult studies have demonstrated elevation of C5a and soluble C5b-9 in patients with COVID-19, as well as deposition of activated complement proteins in injured tissues and organs . Previous reports determined that MIS-C and acute COVID-19 children were associated with highly elevated levels of activation markers of the classical, alternative, and terminal pathways . Children with SARS-CoV-2 infection exhibited elevated levels of soluble C5b9, which correlated with disease severity .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous adult studies have demonstrated elevation of C5a and soluble C5b-9 in patients with COVID-19, as well as deposition of activated complement proteins in injured tissues and organs . Previous reports determined that MIS-C and acute COVID-19 children were associated with highly elevated levels of activation markers of the classical, alternative, and terminal pathways . Children with SARS-CoV-2 infection exhibited elevated levels of soluble C5b9, which correlated with disease severity .…”
Section: Introductionmentioning
confidence: 94%
“…11,20 Previous reports determined that MIS-C and acute COVID-19 children were associated with highly elevated levels of activation markers of the classical, alternative, and terminal pathways. 21,22 Children with SARS-CoV-2 infection exhibited elevated levels of soluble C5b9, which correlated with disease severity. 13,[22][23][24][25] However, there remains a paucity of information on the degree and the possible involvement of complement in the pathogenesis of MIS-C and acute COVID-19 in children, especially from low middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Since C5b-9 levels were shown to correlate with disease severity in both cohorts ( 40 , 49 ), and all non-survivors except from one belonged to the severe COVID-19 group (SEV), the comparison was repeated with further stratifying according to the two severity groups. As seen in Supplementary Figure 6 , disease severity does indeed confound the analysis, since C5b-9 levels did not differ significantly anymore between severely infected survivors (alive) and non-survivors (deceased).…”
Section: Resultsmentioning
confidence: 99%
“…Even though the most common cause of TMA in children is infection with Shiga toxin producing E. coli (STEC), complement-mediated TMA should not be overlooked, especially considering novel triggers for development of hemolytic uremic syndrome (HUS), a common representative of complement-mediated TMA in children ( 5 8 ). Moreover, MIS-C, one of the more serious complications of COVID-19 in children likewise presents with features of TMA paired with complement activity dysregulation ( 2 , 9 , 10 ) ( Table 1 ). This denotes not only a possible diagnostic dilemma, considering the similarities of both HUS and MIS-C, especially when presenting with acute kidney injury (AKI), but also a challenge in timely selection of the most appropriate therapeutic modality.…”
Section: Introductionmentioning
confidence: 99%